Relationship of Albumin Concentrations with Sodium, Potassium, in CAPD (Continuous Ambulatory Peritoneal Dialysis) Patients at PHC Hospital Surabaya - Dian Anggraini; Edy Haryanto; Syamsul Arifin; Ayu Puspitasari (Universitas Nahdlatul Ulama Surabaya, 2022)
Kidney failure is caused by a permanent decline in kidney function and requires renal replacement therapy, one of which is Continuous Ambulatory Peritoneal Dialysis (CAPD). This study aimed to determine the relationship between albumin concentrations and sodium and potassium concentrations in CAPD patients. The study was carried out between January to May 2022. Cross-sectional research methodology is used in this study. It included 60 chronic kidney failure patients who had CAPD as therapy at PHC Surabaya Hospital. Then, patients were divided into three groups with an age interval of 40-50 years, 51-60 years, and 61-70 years in. The results of grouping CAPD patients according to the characteristics based on the age of CAPD patients aged 61-70 years had low albumin concentrations and low sodium concentrations A total of 12 people (66.67%), patients with large CAPD aged 51-60 years, had low albumin and potassium concentrations, namely 11 people (61.11%). CAPD patients aged 51-60 years mostly had low albumin and sodium concentrations in 13 people (72.22%). the conclusion is that in patients with renal failure on CAPD therapy, there is a decrease in albumin and sodium-potassium concentrations due to peritonitis (inflammation) which is associated with a measurable excess of fluid (overhydration) which causes more dilute sodium, causing hyponatremia and hypokalemia.